A barrier model for metal-SiC contact system. (April 2020) - Huang, Lingqin; Tao, Huawen; Ma, Yue; Gu, Xiaogang
Abstract: A theoretical barrier model for metal-SiC contact system has been developed. The effects of surface states density ( D s ) and doping concentration ( N d ) on the barrier height of typical Ti and Pt contacts were calculated and discussed. It is shown that the barrier height of metal/SiC is significantly reduced as N d increases when the surface Fermi level is partially pinned. By considering the barrier inhomogeneities, the barrier properties of Ti and Pt contact to SiC at different N d with different D s were also experimentally investigated. The experimental results are well in agreement with the calculations from the delivered barrier height model. The proposed model provides a perspective to estimate and explain the barrier properties of real metal/SiC structures. Highlights: The charge neutrality level is not coincident with the SiC surface Fermi level. A modified barrier model for metal n-type SiC systems is developed. With partial-pinned Fermi level, the barrier is much reduced as doping increases. The experimental results obey the delivered barrier height model.